2008
DOI: 10.1021/jp804176v
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Studies of the Hydrolysis of Aluminum (Chloro)Hydroxide in Water with CPMD and COSMO

Abstract: Car-Parrinello molecular dynamics (CPMD) and the static density functional method (DFT) with a conductor-like screening model (COSMO) were used to investigate the chemistry of aluminum (chloro)hydroxide in water. With these methods, the stability, reactivity, and acidic nature of the chosen chlorohydrate were able to be determined. Constrained molecular dynamics simulations were used to investigate the binding of chlorine in an aquatic environment. According to the results, aluminum preferred to be 5-fold-coor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 46 publications
2
20
0
Order By: Relevance
“…However, density functional theory (DFT) based on quantum chemistry can overcome the experimental limitation and has been confirmed to be a credible way to study the structure or reaction mechanism of Al(III) species and other compounds. [24][25][26][27][28] Moreover, our previous work found that DFT calculations on the structure formation of oligomers in aluminum sols prepared from basic aluminum acetate were in agreement with the experimental results. [17] Therefore, DFT calculation is a very suitable theoretical method for studying the structure of AC sol.…”
supporting
confidence: 77%
“…However, density functional theory (DFT) based on quantum chemistry can overcome the experimental limitation and has been confirmed to be a credible way to study the structure or reaction mechanism of Al(III) species and other compounds. [24][25][26][27][28] Moreover, our previous work found that DFT calculations on the structure formation of oligomers in aluminum sols prepared from basic aluminum acetate were in agreement with the experimental results. [17] Therefore, DFT calculation is a very suitable theoretical method for studying the structure of AC sol.…”
supporting
confidence: 77%
“…(6) Aluminium chlorohydrate (Saukkoriipi & Laasonen, 2008): It is a group of specific aluminium salts, commercially manufactured by reacting aluminium with hydrochloric acid. The FDA considers that up to 25% concentration is safe in antiperspirants.…”
Section: Additives In Cream and Pastementioning
confidence: 99%
“…During the DFT calculation, to make the theoretical research closer to the experimental results, various continuum models have been applied to consider the solvent effects. White et al studied the Gibbs free energies of deprotonation and dimerization reactions occurring in silicate solution and aluminosilicate solution by DFT method with a conductor-like screening model (COSMO). Their results are basically consistent with existing experimental values and trends, thus proving that accurate replication of solution environments is essential for obtaining useful theoretical results of dissolved species in nonideal environments.…”
Section: Introductionmentioning
confidence: 99%
“…Their results are basically consistent with existing experimental values and trends, thus proving that accurate replication of solution environments is essential for obtaining useful theoretical results of dissolved species in nonideal environments. Saukkoriipi and Laasonen studied the hydrolysis of aluminum (chloro) hydroxide in water by DFT with CPMD and COSMO solvation models. By comparing the results of CPMD and COSMO, it is found that the two methods are complementary.…”
Section: Introductionmentioning
confidence: 99%